Production and partial characterization of dehairing alkaline protease from Bacillus subtilis AKAL7 and Exiguobacterium indicum AKAL11 by using organic municipal solid wastes. Issue 6 (June 2018) - Hakim, Al; Bhuiyan, Farhana Rumzum; Iqbal, Asif; Emon, Tanvir Hossain; Ahmed, Jahed; Azad, Abul Kalam
Abstract: Alkaline proteases have applications in numerous industries. In this study, we have isolated and screened proteolytic bacteria from poultry wastes mixed soil and identified two bacterial isolates as Bacillus subtilis AKAL7 and Exiguobacterium indicum AKAL11 based on 16S rDNA sequencing. Maximum level of protease production was achieved after 24 h of fermentation in a basal medium. The optimal temperature, initial pH of the media and agitation for alkaline protease production by these two isolates were 30 °C, pH 9.0 and 120 rpm, respectively. The both bacterial isolates produced maximum level of protease with 3.0% organic municipal solid wastes (OMSW) as the sole source of carbon and nitrogen under previously optimized fermentation conditions. In comparison with the shake flask, protease production increased about 2.5-fold in the bioreactor with reduction in fermentation period. The partial purification of protease resulted in a final 45.67 and 34.86-fold purified protease with a specific activity of 8335.34 and 9918.91 U/mg protein and a typical yield of 9.75 and 9.41% from B. subtilis and E. indicum, respectively. The optimum temperature and pH of the partially purified protease from the both sources was 40 °C and pH 9.0, respectively. Protease from the both isolates was stable at pH 7.0–12.0 and at temperatures up to 50 °C. The effects of protease inhibitors indicated that the protease from B. subtilis might be serine and cysteine type and from E. indicum might be cysteine type. Mg 2+, K + and Ca 2+ stimulated but Zn 2+, Hg 2+, Co 2+ and Fe 3+ strongly inhibited the protease activity. The partially purified protease from B. subtilis substantially dehaired cow skin and decomposed gelatinous compound from X-ray film. Our study revealed that OMSW can be used as raw material for production of bacterial extracellular protease and alkaline protease from B. subtilis might be potential for industrial and biotechnological applications.